The impact of IP box regimes on the M&A market - Bradley, Sebastien; Robinson, Leslie; Ruf, Martin (Journal of Accounting and Economics, 2021)
Intellectual property (IP) box regimes reward ownership of successful technology by imposing lower tax rates on income derived from IP relative to other sources of business income. Coupled with explicit provisions regarding the eligibility of acquired IP, IP boxes may affect merger and acquisition (M&A) incentives through multiple channels. Applying panel difference-in-differences, triple-differencing, and event study methods, we examine the effects of these modified incentives on the volume of M&A transactions and acquisition probabilities. In regimes with strict nexus requirements, reduced taxation of IP income is associated with reductions in the number of deals and the probability of being acquired for patent-owning firms due to the potential loss of eligibility for preferential taxation. This effect dissipates where nexus requirements are relaxed, and significant positive effects of IP box tax savings in more permissive regimes point to increased after-tax valuations of merger-driven synergies.